2016
DOI: 10.1001/jamadermatol.2015.4233
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Hereditary Infundibulocystic Basal Cell Carcinoma Syndrome Associated With a GermlineSUFUMutation

Abstract: CONCLUSIONS AND RELEVANCE A germline SUFU mutation was present in a patient with MHIBCC, and additional acquired SUFU mutations underlie the development of infundibulocystic basal cell carcinomas. The downstream location of the SUFU gene within the sonic hedgehog pathway may explain why its loss is associated with relatively well-differentiated tumors and suggests that MHIBCC will not respond to therapeutic strategies, such as smoothened inhibitors, that target upstream components of this pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 14 publications
4
61
2
1
Order By: Relevance
“…Although the risk of BCC from a SUFU mutation may be lower than that from a PTCH1 mutation, seven of nine (78%) patients with SUFU variants in the current study had developed BCCs,18 and two (22%) had developed more than 20 BCCs, including one individual (n=45 BCCs) who had not undergone radiotherapy. There are also reports of SUFU pathogenic variants in patients with GS,19 30 31 and an individual with hereditary infundibulocystic BCC has also been reported with a splicing mutation in SUFU 32. Meningiomas also appear more commonly in individuals with SUFU variants, although both in the current series had undergone radiotherapy for medulloblastoma.…”
Section: Discussionmentioning
confidence: 51%
“…Although the risk of BCC from a SUFU mutation may be lower than that from a PTCH1 mutation, seven of nine (78%) patients with SUFU variants in the current study had developed BCCs,18 and two (22%) had developed more than 20 BCCs, including one individual (n=45 BCCs) who had not undergone radiotherapy. There are also reports of SUFU pathogenic variants in patients with GS,19 30 31 and an individual with hereditary infundibulocystic BCC has also been reported with a splicing mutation in SUFU 32. Meningiomas also appear more commonly in individuals with SUFU variants, although both in the current series had undergone radiotherapy for medulloblastoma.…”
Section: Discussionmentioning
confidence: 51%
“…As expected, Sufu-depleted Xenopus embryos develop severely reduced eyes (Min et al, 2011). In humans, inherited and sporadic mutations in SUFU have been identified in a wide variety of cancers, including medulloblastoma (Taylor et al, 2002;Brugieres et al, 2010), meningioma (Aavikko et al, 2012) and basal cell carcinoma (Pastorino et al, 2009;Kijima et al, 2012;Schulman et al, 2015). Interestingly, in contrast to Sufu in other vertebrate species, zebrafish Sufu is a weak Hh inhibitor, and knockdown of Sufu causes only a marginal increase in Hh signaling during zebrafish embryonic development (Wolff et al, 2003).…”
Section: Introductionsupporting
confidence: 55%
“…Loss of Sufu elevates vertebrate Hh signaling and induces severe patterning defects during development (Wolff et al, 2003;Cooper et al, 2005;Svard et al, 2006;Min et al, 2011). In humans, oncogenic mutations in SUFU have been identified from medulloblastoma, basal cell carcinoma and other cancers (Taylor et al, 2002;Pastorino et al, 2009;Brugieres et al, 2010;Aavikko et al, 2012;Kijima et al, 2012;Schulman et al, 2015). Despite the fundamental roles played by Sufu in development and cancer, it is largely unclear how the Sufu protein itself is regulated.…”
Section: Discussionmentioning
confidence: 99%
“…Such mutations are likely due to mutations occurring downstream of SMO at the level of GLI2 or SUFU . For this reason, multiple hereditary infundibulocystic basal cell carcinoma (MHIBCC), which is associated with a germline SUFU mutation, does not respond to SMO inhibitors that target upstream of the mutated SUFU gene in this case . Sharpe et al found a loss‐of‐function mutation in a PI3K pathway regulator, phosphatase and tensin homologue (PTEN), which has been previously implicated in lowering response to vismodegib treatment in MB models .…”
Section: Interventionsmentioning
confidence: 99%